Community-Based and Eco-Friendly Palm Oil Industry Waste Management Model: for Community Business - Kasmuddin, Kasmuddin; harahab, nuddin; warsito, warsito; haris, abdul (Archives of Business Research, 2020)
This study aims to formulate strategy and model for managing the palm oil industry solid waste. The sample was taken by conducting purposive sampling; it included the community around the industry that represented the existing socio-culture, and some company employees. The data collection techniques were Interview, Observation, and Focus Group Discussion (FGD). The data analysis of the palm oil industry waste management policy strategy was carried out by using SWOT. Then, a community-based and eco-friendly palm oil industry waste management model was formulated. The results revealed that the community that processed the palm oil industry waste was internally weak, but it still had some opportunities. The recommended strategy is conservative. Community-based solid waste management requires the involvement and role of various parties such as government, private sector, the role of technology, researchers, and social media. The government can give its support through regulations and facilitation to improve the ability of human resources in mastering waste utilization technology. Meanwhile the private sector can be the catalyst to build brand image and brand awareness.